The Sanctions on Environmental Performances: An Assessment of Indonesia and Brazilia Practice - M Zaid; M. Musa; Fadhel Arjuna Adinda; Lamberton Cait (Lembaga Contrarius Indonesia, 2023)
This study aims to offer an overview of the effect of environmental law sanctions, particularly criminal sanctions for restoring environmental functions for firms, on restoring environmental functions in Indonesia and Brazil. Using conceptual techniques, statutory methodologies, and comparative legal approaches with Brazil, this study examines how norms emerge in the law. The research shows that criminal sanctions for environmental function restoration in Indonesia have not had their full intended effect and often lead to confusion over their implementation since they do not specify a means of gauging whether or not their goals have been met. This discovery also suggests that criminal consequences for environmental function restoration have not been utilized to their full potential. This is because criminal sanctions do not offer a mechanism for gauging the degree to which ecological restoration efforts have been fruitful. Brazil, which is more likely to apply administrative sanctions and has a better impact, conducts a wide range of things, including imposing fines, canceling company licenses, and other preventative steps used to anticipate excessive environmental exploitation. Brazil has taken these precautions to avoid the negative effects of environmental overexploitation. The actions are in effect to ensure that environmental exploitation does not reach unsustainable levels.